1996
DOI: 10.1074/jbc.271.32.19288
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the α Chain Lysine Donor Sites Involved in Factor XIIIa Fibrin Cross-linking

Abstract: Biochemical studies of fibrin cross-linking were conducted to identify the specific A␣ chain lysine residues that potentially serve as Factor XIII a amine donor substrates during ␣ polymer formation. A previously characterized Factor XIII a fibrin lysine labeling system was employed to localize sites of donor activity based on their covalent incorporation of a synthetic peptide acceptor substrate analog modelled after the NH 2 -terminal cross-linking domain of ␣ 2 antiplasmin. Peptide-decorated fibrin was prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(42 citation statements)
references
References 45 publications
(34 reference statements)
2
40
0
Order By: Relevance
“…Fraction I-9 fibrinogen was prepared as described (30). Fibrinogen molecules in this preparation lack Ϸ100 or more C-terminal A␣ chain residues (31), which contain almost all of the lysine amine donor sites (16,17), and therefore they do not participate in ␣ chain crosslinking of fibrin (32). ␥ chain dimerization is, however, slightly slower but otherwise normal (1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fraction I-9 fibrinogen was prepared as described (30). Fibrinogen molecules in this preparation lack Ϸ100 or more C-terminal A␣ chain residues (31), which contain almost all of the lysine amine donor sites (16,17), and therefore they do not participate in ␣ chain crosslinking of fibrin (32). ␥ chain dimerization is, however, slightly slower but otherwise normal (1).…”
Section: Methodsmentioning
confidence: 99%
“…␥ chain crosslinking occurs solely between these residues (2-4, 15, 16), whereas there are several amine donor lysine and amine acceptor glutamine sites in A␣ chains (16,17). Primary amine compounds like cadaverine are competitive amine donor substrates that become specifically incorporated in the presence of factor XIIIa at the single ␥ chain acceptor site or at one or more ␣ chain acceptor sites (2-4, 15, 18, 19).…”
Section: Introductionmentioning
confidence: 99%
“…The x-ray crystal structure of the D-fragment shows that the ␣-chain doubles back upon itself, apposing the A␣-chain residues of 113-126 of the TSP1 binding site to three potential cross-link sites, Lys 208 , Lys 219 , and/or Lys 224 (56). Lys 208 , Lys 219 , and Lys 224 all were found cross-linked to the ␣ 2 -antiplasmin peptide, although none were a preferred site (used only 2-5% of the time) (55). The results are consistent with P123 binding to region(s) within the D-domain as directed by P123 and cross-linking to Lys 208 , Lys 219 , and Lys 224 within the D-domain via the flexible amino-terminal tail derived from GE1.…”
Section: Incorporation Of Procollagen and Properdin Fusion Proteins Imentioning
confidence: 99%
“…A␣ chains then polymerize to form higher molecular mass polymers; this reaction occurs more slowly than ␥-␥ dimer formation (4). Many lysine residues have been implicated as substrates for crosslinking and subsequent generation of high molecular mass oligomers of A␣ chain (5,6). It has been found that multimerization of ␥-␥ dimers can occur over extended time periods (7).…”
mentioning
confidence: 99%